Dampak Kerjasama Kontraterorisme Filipina – Amerika Serikat di Mindanao (2022-2023) - Agista, Senia Nur; Argenti, Gili (Journal of Integrative International Relations, 2025)
This study analyzes the impact of Philippine-US counterterrorism cooperation in Mindanao during the period 2022–2023, using a neoliberal institutionalism approach and the concept of international regimes. The results show that cooperation between the two countries not only survived after the US withdrawal from Afghanistan, but actually intensified through the strengthening of legal frameworks such as EDCA, joint military exercises, and intelligence and capacity building support. This cooperation is symbiotic: the Philippines receives security and economic support, while the US strengthens its influence in the Indo-Pacific region. Although the counterterrorism approach is still dominated by military aspects, there are efforts to address the root causes of the conflict through civil-military programs. This study concludes that the institutionalized cooperation regime has succeeded in creating stability and trust, although its sustainability depends on the ability of both countries to integrate security approaches with economic development in Mindanao.